Investigation of Polymer/Ceramic Composite Solid Electrolyte System : The Case of PEO/LGPS Composite Electrolytes - Li, Meirong; Kolek, Martin; Frerichs, Joop Enno; Sun, Wei; Hou, Xu ; 0000-0003-0398-2006; Hansen, Michael Ryan; Winter, Martin; Bieker, Peter (ACS Sustainable Chemistry and Engineering, 2021)
The incorporation of inorganic lithium superionic conductors in polymer/ceramic composite electrolytes has been frequently proposed since this approach is expected to take advantage of the high ionic conductivities of the lithium superionic conductors and the elasticity of the polymer constituents of the composites. Nevertheless, the properties and mechanisms of polymer/ceramic composite electrolytes are yet to be comprehensively investigated. In this work, we systematically study sulfide-based polymer/ceramic composites from the aspects of composition dependence, electrochemical performance, and chemical stability. The composition-dependent Li-ion conduction mechanism and electrochemical behavior have been revealed for polyethylene oxide/Li10GeP2S12 composite electrolytes, highlighting the rational selection of compositions of polymer/ceramic composites toward desired functions. Furthermore, the chemical stability of the sulfide electrolyte in diverse solvent media as well as the potential internal reactions between the components of the composite electrolyte have been investigated, which underline the chemical stability consideration in the design and fabrication of the composite electrolyte. Thus, this work aims at contributing to the design and fabrication of sulfide-based polymer/ceramic composite electrolytes that enable high-performance lithium metal batteries.
Publisher Copyright: © 2021 The Authors. Published by American Chemical Society.
Keywords: (polymer/ceramic composite electrolyte; electrochemical and chemical stability; lithium conducting mechanisms; solid-state batteries); sulfides